Ultrasonic versus high-speed cavity preparation: Analysis of increases in pulpal temperature and time to complete preparation - Vanderlei, Aleska Dias [UNESP]; Souto Borges, Alexandre Luiz [UNESP]; Cavalcanti, Bruno Neves; Rode, Sigmar Mello [UNESP] (Mosby-elsevier, 2008)
Statement of problem. The use of ultrasonic tips has become an alternative for cavity preparation. However, there are concerns about this type of device, particularly with respect to intrapulpal temperatures and cavity preparation time.Purpose. The purpose of this study was to analyze pulpal temperature increases generated by an ultrasonic cavity preparation with chemical vapor deposition (CVD) tips, in comparison to preparation with a high-speed handpiece with a diamond rotary cutting instrument. The time required to complete the cavity preparation with each system was also evaluated.Material and methods. Thermocouples were positioned in the pulp chamber of 20 extracted human third molars. Slot-type cavities (3 x 3 x 2 mm) were prepared on the buccal and the lingual surfaces of each tooth. The test groups were: high-speed cavity preparation with diamond rotary cutting instruments (n = 20) and ultrasonic cavity preparation with CVD points (n = 20). During cavity preparation, the increases In pulpal temperature, and the time required for the preparation, were recorded and analyzed by Student's t test for paired samples (alpha = .05).Results. The average pulpal temperature increases were 4.3 degrees C for the high-speed preparation and 3.8 degrees C for the ultrasonic preparation, which were statistically similar (P = .052). However, significant differences were found (P < .001) for the time expended (3.3 minutes for the high-speed bur and 13.77 minutes for the ultrasound device).Conclusions. The intrapulpal temperatures produced during cavity preparation by ultrasonic tips versus high-speed bur preparation were similar. However, the use of the ultrasonic device required 4 times longer for the completion of a cavity preparation.